Multinational Corporation Strategies, Human Resource Management Practices and Competitive Advantage: The Rubber Industry in Thailand - Chanin, Oraphan (2010)
Multinational corporations have become increasingly ascendant in the world economy. In order to survive and to achieve profitability, multinational corporations need to create and to sustain competitive advantage. The source of competitive advantage are from both internal and external factors. For the firms competing in the same industry, internal factors such as strategy, management practices, corporate structure, etc. play a major role in the firms' success. This study investigates the relationship between multinational corporation strategies and human resource management practices, which are critical in gaining competitive advantage. This study attempts to combine these three concepts and empirically investigated the proposed framework in the Thai rubber industry by selecting only the multinational corporations. The rubber multinational companies that had participated in this study had consisted of based on Department of Business Development (DBD) in Thailand. Expert interview was used as an instrument for pilot test and to check the questionnaire. The mail survey was employed to collect data. A total of 94 multinational companies had participated in the questionnaire surveys. The findings of this study revealed that national responsiveness strategy had negative relationship with competitive advantage and global integration with local responsiveness strategy had positive relationship with competitive advantage. Moreover, employee security, reward system at performance level and employee participation had positive relationship with innovation and selection by job competency, reward system at performance level and employee participation had positive relationship with productivity. In addition, the research had also compared the difference between multinational corporation strategies and human resource management practices. It was found that different multinational corporation strategies lead to different selection by job competence, employee security, clarity of work, reward system at performance level, employee participation and employee contribution. The academic, managerial, and policy implications, limitation of the research of the research and suggestion for further research sere also explained.